P589Mediastinal adipose stem cells improve contractile function of failing hearts. (15th July 2014) - Chao, C; Xiang, B; Deng, JX; Lin, HY; Natarajan, K; Lin, F; Liu, HY; Freed, DH; Arora, RC; Tian, GH
Abstract: This abstract is embargoed until 4 July, 0930 Central European Time.